Big Changes, Big Characters: Public Development Discourse in Yunnan, China - Couper, John Lord; Litang, Cui (Jurnal Studi Komunikasi, 2018)
In China, ‘Big Character’ posters have represented public discourse for centuries, now updated as billboards, posters, and banners. This study analyzes public discourse on development and politics to understand representations of tradition, globalization and modernization in Yunnan Province, China. Signage by authorities, corporations, and community groups ranges from paper calligraphy to Internet dissent. The authors used Social Semiotics to investigate explicit and implicit codes, both verbal and visual on three levels. Government signage aligns citizens with governmental values, actions, and politics. Commercial signage strengthens community acceptance of development. Community signage gently criticizes local government and requests help. Results indicated that community members enjoyed unusual, if circumscribed, freedom to comment and criticize. The authors theorize various functions of public discourses on development in a region that is experiencing dramatic change and resistance. The study also suggests a framework for analyzing public discourse.